Degenerative cervical myelopathy: timing of surgery - Maria Rossella Fasinella; Alberto Benato; Donato Creatura; Alexis Morgado; Cédric Yves Barrey (EFORT Open Reviews)
Background: Despite the growing burden of degenerative cervical myelopathy (DCM), consensus on the optimal timing of surgical intervention remains lacking, especially for patients with mild symptoms or asymptomatic cord compression or in the context of recent trauma. Different scores, such as the mJOA, Nurick scale and NDI are commonly used to classify disease severity, but guidelines for managing these patients do not provide a clear framework for intervention timing. Materials and methods: We conducted a narrative review of the literature on the optimal timing of surgical intervention for DCM, using PubMed to identify relevant studies. The search was focused on surgical and non-operative management, clinical and radiological assessments, biomarkers and emerging technologies. The selected papers were reviewed for relevance and quality, with guidance from a senior author. Results: The initial search identified 6,705 articles, which were narrowed down to 136 relevant studies after applying filters for study type and clinical focus. A final selection of 87 papers was categorized by topics and the findings were synthesized to highlight trends, challenges and knowledge gaps in surgical timing for DCM. Focus of the study: This review article examines strategies for determining the optimal timing for surgery in DCM. It explores how radiological signs, clinical indicators and other markers may help identify patients at risk of rapid neurological deterioration, particularly in the ‘grey-zone’ population (mild symptoms or asymptomatic disease), enabling clinicians to assess correctly different clinical scenarios and to indicate timely surgical intervention.